Perceptions of school science teachers who implement TMF on the independent curriculum implementation - Ni Wayan Karlina; Sauqina Sauqina; Rizky Febriyani Putri; Maya Istyadji (HAFECS PRESS, 2024)
This research serves as initial information about the aspects that determine the teacher's teaching process regarding perceptions of implementing the Teaching Mastery Framework (TMF) in supporting the independent learning curriculum in the middle school A scientific environment, and be a reference in adjusting teacher competency improvement programs implemented by school principals in the future. The research aims to determine the perceptions of science teachers at middle school A in improving the quality of teachers' teaching practices as evaluation material for teachers in implementing TMF and the role of TMF in supporting the independent learning curriculum. This research uses a qualitative approach. This type of research is a case study. Case study research may focus on programs, events, or actions involving individuals rather than the group. Additionally, when case studies study groups, they may be more interested in explaining their activities than in identifying the typical patterns of behavior they exhibit. The data collection techniques used were interviews, observation, and documentation. The sampling technique uses purposive sampling. Data analysis techniques use source triangulation and engineering triangulation. The research results show that teachers' perceptions of implementation improve teaching practices with TMF, namely freedom in teaching, so the methods and models used to deliver material to students more varied. The TMF aspect role of middle school A increase teacher competence and provide convenience for teachers in independent curriculum implementing, in line with the TMF that the school has in the classroom and administratively to improve the quality of teacher teaching. Keyword: teaching mastery framework; middle school; perception; teachers; natural science Abstrak. Penelitian ini menjadi informasi awal mengenai aspek-aspek yang menentukan proses mengajar guru terkait persepsi terhadap implementasi Teaching Mastery Framework (TMF) dalam mendukung pembelajaran Kurikulum Merdeka di lingkungan saintifik SMP A, dan menjadi acuan dalam menyesuaikan program peningkatan kompetensi guru yang dilaksanakan oleh kepala sekolah di masa yang akan datang. Penelitian ini bertujuan untuk mengetahui persepsi guru IPA di SMP A dalam meningkatkan kualitas praktik mengajar guru sebagai bahan evaluasi bagi guru dalam mengimplementasikan TMF dan peran TMF dalam mendukung pembelajaran Kurikulum Merdeka. Penelitian ini menggunakan pendekatan kualitatif. Jenis penelitian ini adalah studi kasus. Penelitian studi kasus dapat berfokus pada program, peristiwa, atau tindakan yang melibatkan individu daripada kelompok itu sendiri. Selain itu, ketika studi kasus mempelajari kelompok, mereka mungkin lebih tertarik untuk menjelaskan kegiatan mereka daripada mengidentifikasi pola umum perilaku yang mereka tunjukkan. Teknik pengumpulan data yang digunakan adalah wawancara, observasi dan dokumentasi. Teknik pengambilan sampel menggunakan purposive sampling. Teknik analisis data menggunakan triangulasi sumber dan triangulasi teknik. Hasil penelitian menunjukkan bahwa persepsi guru terhadap implementasi meningkatkan praktik mengajar dengan TMF, yaitu adanya kebebasan dalam mengajar, sehingga metode dan model dalam menyampaikan materi kepada siswa lebih variatif. Peran aspek TMF SMP A meningkatkan kompetensi guru dan memberikan kemudahan bagi guru dalam melaksanakan Kurikulum Merdeka, yang juga sejalan dengan TMF yang dimiliki sekolah di dalam kelas dan secara administratif dalam rangka meningkatkan kualitas mengajar guru.